Investigation of the molecular mechanisms which contribute to the survival of the polychaete Platynereis spp. under ocean acidification conditions in the CO2 vent system of Ischia Island (Italy) - Silvia Giorgia Signorini; Marco Munari; Antonio Cannavacciuolo; Matteo Nannini; Diletta Dolfini; Antonia Chiarore; Fiorenza Farè; Manuela Fontana; Donatella Caruso; Maria Cristina Gambi; Camilla Della Torre (Frontiers in Marine Science, 2023)
The continuous increase of CO2 emissions in the atmosphere due to anthropogenic activities is one of the most important factors that contribute to Climate Change and generates the phenomenon known as Ocean Acidification (OA). Research conducted at the CO2 vents of Castello Aragonese (Ischia, Italy), which represents a natural laboratory for the study of OA, demonstrated that some organisms, such as polychaetes, thrive under acidified conditions through different adaptation mechanisms. Some functional and ecological traits promoting tolerance to acidification in these organisms have been identified, while the molecular and physiological mechanisms underlying acclimatisation or genetic adaptation are still largely unknown. Therefore, in this study we investigated epigenetic traits, as histone acetylation and methylation, in Platynereis spp. individuals coming from the Castello vent, and from a nearby control site, in two different periods of the year (November-June). Untargeted metabolomics analysis was also carried out in specimens from the two sites. We found a different profile of acetylation of H2B histone in the control site compared to the vent as a function of the sampling period. Metabolomic analysis showed clear separation in the pattern of metabolites in polychaetes from the control site with respect to those from the Castello vent. Specifically, a significant reduction of lipid/sterols and nucleosides was measured in polychaetes from the vent. Overall results contribute to better understand the potential metabolic pathways involved in the tolerance to OA.